2009
DOI: 10.1002/icd.647
|View full text |Cite
|
Sign up to set email alerts
|

Influences of information processing and disengagement in infants' looking behaviour

Abstract: The present study considers the joint influences of information processing and disengagement in looking behaviour within a habituation paradigm. Six-month-old infants were habituated, during which their heart rate (HR) was measured. A parametric model of habituation yielded for each infant parameter estimates of their habituation performance. These parameters were interpreted as assessing information processing and disengagement. Corresponding measures were obtained from the HR data. The HR measures and habitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…According to these findings, infant fixation behavior during habituation reflects stimulus encoding (sustained attention) as well as inhibitory processes (attention termination). Domsch, Lohaus, and Thomas (2010a) confirmed these results with infants 6 months of age. Domsch et al (2010a) and Domsch, Lohaus, and Thomas (2010b) also found that an attention-getter, an attractive stimulus which redirects the infant's attention to the stimulus display, shown before each habituation trial elicited an orienting response and a heart rate decrease.…”
Section: Heart Rate Measurementsupporting
confidence: 77%
See 2 more Smart Citations
“…According to these findings, infant fixation behavior during habituation reflects stimulus encoding (sustained attention) as well as inhibitory processes (attention termination). Domsch, Lohaus, and Thomas (2010a) confirmed these results with infants 6 months of age. Domsch et al (2010a) and Domsch, Lohaus, and Thomas (2010b) also found that an attention-getter, an attractive stimulus which redirects the infant's attention to the stimulus display, shown before each habituation trial elicited an orienting response and a heart rate decrease.…”
Section: Heart Rate Measurementsupporting
confidence: 77%
“…According to these findings, infant fixation behavior during habituation reflects stimulus encoding (sustained attention) as well as inhibitory processes (attention termination). Domsch, Lohaus, and Thomas () confirmed these results with infants 6 months of age.…”
Section: The Contribution Of Physiological Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…Whilst some of these models have investigated different aspects of visual orienting in infancy (Carlson & Triesch, 2004;Schlesinger, Amso, & Johnson, 2007;Domsch et al, 2010;Sirois & Mareschal, 2002; for a review see Mareschal, 2010), to date no computational model has attempted to explain the specific mechanisms underlying saccadic control in infancy.…”
Section: Modeling Infant Fds With the Crisp Modelmentioning
confidence: 99%
“…An alternative interpretation, disengagement theory (Colombo, 1995, 2002), suggests that, rather than reflecting infants’ increasing capability of stimulus encoding, duration of looking at a stimulus display reflects infants’ increasing ability to disengage from a stimulus. Recent research suggests that both stimulus encoding and disengagement contribute to the overall age-related decrement in duration of looking observed during the first year of life (Colombo, Richman, Shaddy, Greenhoot, & Maikranz, 2001; Colombo, Shaddy, Richman, Maikranz, & Blaga, 2004; Domsch, Lohaus, & Thomas, 2008; for a discussion, see Kavšek, in preparation). …”
Section: Infant Visual Habituation and Dishabituationmentioning
confidence: 99%